Attempts to commit suicide by exogenous intoxication with medication in a city of the southeast region of Brazil (Research, Society and Development, 2021)
Introduction: Exogenous intoxication (EI) is the second most commonly used method to commit suicide, preceded by hanging, and is the first in terms of suicide attempts. Objective: To analyze suicide attempts to EI prevalence and the factors associated with this practice in the population of of the municipality of Birigui/SP. Methods: This is a descriptive, retrospective and observational study of the population of the municipality of Birigui. Data obtained by extracting information contained in the database of the Department of Informatics of the Unified Health System (DATASUS ) of the Brazilian Ministry of Health. Using the TabNet Win32 3.0 program, we analyzed data for the period 2013 – 2017, focusing on six variables: race, sex, education, age group, clinical evolution, and type of exposure. Results and conclusions: 296 cases were studied, increase in suicide attempts by EI through medication over the years from 27 cases 2014, culminating in 108 cases in 2017. Most cases were with females in all years (n=35 in 2013, n =27 in 2014, n=35 in 2015, n=51 in 2016 and n=84 in 2017), The highest incidence was found in the 15–19 years population (n = 49) with low education. Acute, single exposure intoxication predominated over others with 53% of cases (n=157) and cure without sequelae was observed in 63.9% of cases (n=189). During this period, there was an increase in suicide attempts due to EI over the years predominantly young women and persons of a low level of education.